Wages withheld, deferred or deflected: The case of child domestic workers in Addis Ababa, Ethiopia - Annabel Erulkar; Lemi Negeri; Eyasu Hailu Mekonnen; Elizabeth Anderson; Yuki Lo (Child Protection and Practice)
Background: Most studies of child domestic workers highlight extreme hardship, abuse and exploitation. Few studies have examined the dynamics of wages/payments among young domestic workers. Objective: The objective is to explore the dynamics of payment between child domestic workers and employers, specifically, factors associated with direct or withheld payments, or payment sent to family members. Participants and setting: This study of child domestic workers took place in selected locations of Addis Ababa, where large numbers were known to be present. Methods: The is a large-scale, mixed-method study, including a quantitative survey of domestic workers, a sub-sample who were interviewed in-depth, and a validation study among former domestic workers. Results: Sixty-seven percent of child domestic workers were paid directly for their services. The remainder had their salary withheld by the employer (28 percent) or sent to the family members (5 percent). Being younger (AOR 2.4, p < 0.001 among age 12–14; AOR 2.5, p < 0.006 among age 15–17) was associated with increased odds of one's employer withholding salary, while having an employment contract was associated with decreased odds of withheld pay (AOR 0.6, p < 0.002). Those who were placed in work by family members were over five times more likely (AOR 5.1, p < 0.001) to have payment sent to families. Conclusions: Our research underscores the importance of enforcement of child labor laws and laws related to ‘young workers.’ Among those of legal working age, our results underscore the need for formal employment contracts, increased legal protection and improved working conditions for domestic workers.